Comparative evaluation of sequencing platforms: Pacific Biosciences, Oxford Nanopore Technologies, and Illumina for 16S rRNA-based soil microbiome profiling - Veselovsky, Vladimir; Romanov, Mikhail; Zoruk, Polina; Larin, Andrey; Babenko, Vladislav; Morozov, Maxim; Strokach, Aleksandra; Zakharevich, Natalia; Khamidova, Sadokatkhon; Danilova, Albina; Vatlin, Aleksey; Pavshintsev, Vsevolod; et al. (Frontiers in Microbiology, 2025)
Soil microbiome profiling is crucial for understanding microbial diversity and its roles in ecosystem functioning and agricultural productivity. Recent advancements in high-throughput sequencing, particularly Pacific Biosciences (PacBio) and Oxford Nanopore Technologies (ONT), offer long-read sequencing capabilities that enhance microbial community analysis. In this study, we performed a comparative evaluation of 16S rRNA gene sequencing using Illumina (V4 and V3–V4 regions), PacBio (full-length and trimmed V3–V4/V4 regions), and ONT (full-length) to assess bacterial diversity in soil microbiomes. We analyzed three distinct soil types and applied standardized bioinformatics pipelines tailored to each platform. To ensure comparability, sequencing depth was normalized across platforms (10,000, 20,000, 25,000, and 35,000 reads per sample). Our results demonstrated that ONT and PacBio provided comparable bacterial diversity assessments, with PacBio showing slightly higher efficiency in detecting low-abundance taxa. Despite differences in sequencing accuracy, ONT produced results that closely matched those of PacBio, suggesting that ONT’s inherent sequencing errors do not significantly affect the interpretation of well-represented taxa. Our study demonstrated that, regardless of the sequencing technology used and the choice of the target region (full-length 16S rRNA gene or its regions), microbial community analysis ensures clear clustering of samples based on soil type. The only exception is the V4 region, where no soil-type clustering is observed (p = 0.79). These results provide a comprehensive evaluation of sequencing platform performance.